GazeBase, a large-scale, multi-stimulus, longitudinal eye movement dataset - Henry Griffith (Nature Portfolio, 2021)
Measurement(s) eye movement measurement Technology Type(s) eye tracking device Factor Type(s) round • participant Sample Characteristic - Organism Homo sapiens Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14761866